HUBUNGAN ANTARA KEBERHASILAN KOPERASI DAN MANAJEMEN ORGANISASI DENGAN PARTISIPASI ANGGOTA KOPERASI JAYA BERSAMA IKATAN KELUARGA KUANTAN SINGINGI (IKKS) KECAMATAN TANAH MERAH KABUPATEN INDRAGIRI HILIR - Safitri, Intan Mega; Makhdalena, Makhdalena; Mujiono, Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to: 1) determine the relationship between the success of the cooperative and the participation of members of the Jaya Bersama Cooperative Ikatan Keluarga Kuantan Singingi (IKKS) Tanah Merah Subdistrict, Indragiri Hilir Regency; and 2) knowing the relationship between organizational management and the participation of members of the Jaya Bersama Ikatan Keluarga Kuantan Singingi (IKKS) in Tanah Merah Subdistrict, Indragiri Hilir Regency; 3) knowing the relationship between the success of cooperatives and the organizational management of the Jaya Cooperative Together with the Ikatan Keluarga Kuantan Singingi (IKKS) Tanah Merah Subdistrict, Indragiri Hilir Regency; and 4) knowing the relationship between the success of cooperatives and organizational management with the participation of members of the Cooperative Jaya Together with the Ikatan Keluarga Kuantan Singingi (IKKS) Tanah Merah Subdistrict, Indragiri Hilir Regency. The population in this study were all members of the cooperative with a total of 97 people. The sampling technique used a saturated sample so that the entire population of 97 people was the research sample. The data analysis technique used is multiple correlation. The results of the study indicate that the success of cooperatives and cooperative management has a positive and significant relationship to the participation of members of the Jaya Bersama Cooperative Ikatan Keluarga Kuantan Singingi (IKKS) Tanah Merah Subdistrict, Indragiri Hilir Regency.Keywords: Cooperative Success, Organizational Management, and Member Participation